The study of relationship between compressive strength and expansion of alkali silica reaction and/or delayed ettringite formation with the use of fly ash - Sriprasong, Thanadet; Lethaisong, Phakkhaphum; Khum-in, Vinita (Journal of Applied Research on Science and Technology (JARST), 2025)
Mass concrete structures that have been deteriorated are typically attributed to shrinkage or thermal deformation. However, there is another type of cracking that has been found which crack patterns has been considered to the result from alkali-silica reaction (ASR) and/or delayed ettringite formation that occurred in heat-steam cured in massive concrete structures when the initial temperature during hydration process exceeds 70 oC. It is generally believed that the use of fly ash has played an important role in increasing the durability in concrete. This study investigates the effects of fly ash on the compressive strength and expansion of mortar specimens subjected to ASR and/or DEF and water absorption in mortar specimens. Mortar samples were prepared by using Portland cement Type III with 20% replacement of Class F fly ash, some of the specimens contained reactive aggregates as silica sand through a replacement of 30 wt% of river sand. sodium sulfate was added (4 %wt SO3 addition). Some specimens were exposed to an elevated temperature curing at early age to induce ASR and accelerate DEF. Compressive strength and length change were measured over 200 days. Results indicate that fly ash was effective in mitigating ASR expansion but had limited impact on DEF. Samples exposed to both ASR and DEF conditions, the expansion exhibited essential expansion and rapid with the reduction of compressive strength when reactive aggregate and sodium sulfate were used. This research provides insights into the complex interactions between fly ash, ASR, and DEF in cementitious systems, with implications for improving concrete durability in aggressive environments.